The genus Pachylaena (Asteraceae, Mutisieae) - Katinas, Liliana (2008)
The Andean genus Pachylaena (Asteraceae, Mutisieae) comprises perennial, subrosulate to rosulate herbs, with wide, glaucous and crass leaves, all bilabiate corollas, the marginal ones showy, yellow and/or pink and radiating, and plumose pappus. The genus had traditionally two species: P. atriplicifolia and P. rosea. This study shows that P. rosea should be treated as a synonym of P. atriplicifolia because the two characters of distinction, the colour of the corollas and the morphology of the involucre phyllaries, are shared by both taxa. An overview of the genus Pachylaena and its only species P. atriplicifolia is performed here, which includes descriptions, synonymic lists, illustrations, a distribution map, and ecological aspects.